ANALISIS PERILAKU PEMILIH PADA SURVEY PRA PEMILU 2009 MENGGUNAKAN METODE CHAID - KURNIA, LELY (Sainstek : Jurnal Sains dan Teknologi, 2010)
This research studied about the the respondents characteristic at the legislative general pre-election in 2009. The researcher used statistic analysis to see the association and structural connection between variables as the characteristic of voters? behavior. The data used in this study is gotten from the result of a survey on voters? behavior in the form of counting and category data, that?s why the statistic methods used was CHAID. Analysis of CHAID showed that the variables having the strongest association with the party choice is age. CHAID method at the analysis of respondent characteristics of voters in the election resulted in five segments of the party choice of respondents. In each segment, the old party is still the party that is trusted by respondents to represent their voice in parliament.Key words: voting behavior, interaction, chi-square, CHAID method